The CRE tambora.org – new data and tools for collaborative research in climate and environmental history. (19th January 2016) - Riemann, D.; Glaser, R.; Kahle, M.; Vogt, S.
Abstract : Tambora.org is a new web‐based Collaborative Research Environment (CRE) for Historical Climatology (HC) and Environmental research, already containing several huge data collections from different regions with different cultural background. The integration and sustainable storage of existing data collections, as well as the entry of new data are core features of the system. Additionally, tambora.org provides a growing toolbox for creating, analysing and presenting the data. With many active contributors and everyone being invited to add further datasets, it is continuously growing. Tambora.org enables researchers to collaboratively interpret climate information derived from historical sources. It includes tools to support the complete workflow of transforming the raw source material (typically text) to data useful for climatic analysis and finally the publication of data. It provides a database for original text quotations together with bibliographic references and derived searchable, dated and geo‐referenced information on climate and environment. To acknowledge scientific work, tambora.org facilitates the process of assigning citable DOIs (digital object identifier) to data collections by providing the necessary infrastructure and institutional responsibility for quality control.